The benefits of nutritional counselling for improving sport performance - Soldati, L.; Pivari, F.; Parodi, C.; Brasacchio, C.; Dogliotti, E.; De Simone, P.; Rossi, M.; Vezzoli, G.; Paoli, A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: It is well known that the synergy between physical activity and healthy eating habits is an important combination for the achievement of different objectives. However, recent studies in the literature focused mainly on the effect of this synergy on weight loss or different non communicable diseases. In this study, we aimed to investigate the effect of healthy eating, based on the Mediterranean diet, on physical performance of kickboxers and runners. METHODS: Forty athletes were recruited from the University Sports Center of Bergamo. Twenty participants practiced kickboxing, an High Energy Expenditure Rate sport, whereas twenty subjects practiced half marathon, a typical High Energy Expenditure Volume sport. Kickboxers and runners were randomly divided into two sub-groups of ten subjects each: one was the control group (CG) and one the nutritional counselling group (NCG), in which subjects were instructed to follow a nutritional counselling. RESULTS: At the baseline, runners started with greater VO2max and lower resting metabolic rate compared to kickboxers. After three months of controlled diet and training, kickboxers in NCG improved their results in Counter Movement Jump (CMJ) Test (P=0.015) and squat (P=0.012). Moreover, athletes had a decrease in body fat percentage (P=0.008). Runners in NCG, had a significant VO2max (P=0.007) increase and a reduction in body fat percentage (P=0.002). They also showed an increase of squat (P=0.012) and CMJ test (P=0.024). CONCLUSIONS: Significant benefits were achieved in all groups of athletes, but results were maximized by training plus nutritional counselling.